Chapter Tra nord e sud. Le signorie rurali in valle dell'Adige, nella piana Rotaliana e in valle di Cembra - TOMEDI, ANDREA (Reti Medievali E-Book, 2023)
With reference to the 14th and 15th centuries, the essay analyses the specific characteristics of the rural lordships of the Adige valley, on the border between the territory subject to the bishop-prince of Trento and the southern Tyrol.